Service Justice Dimensions As Determinants Toward Satisfaction And Word Of Mouth Behavior - Utiyati Utiyati; Guruh Ghifar Zalzalah; Sri Rejeki Ekasasi; Anas Hidayat (Forum Inovasi Bisnis dan Manajemen, 2022)
The research objectives were to analyze the role of service justice (distributive, procedural, interactional) toward the behavior of Word of Mouth (WOM) which was influenced by the satisfaction of the students over the service conducted by Directorate of Student Affairs of a state university. The population of this study was students of a the biggest state university in Yogyakarta- Indonesia with the number of samples taken as many as 220 students. The sampling technique in this research was purposive sampling. The data analysis technique used Structural Equation Modeling (SEM). The results showed that distributive justice and interactional justice had a positive effect on satisfaction, whereas procedural justice had no positive effect on satisfaction. The satisfaction variable succeeded to be a mediator variable between service justice dimension and word of mouth (WOM) behavior.